2017
DOI: 10.21061/jte.v29i1.a.4
|View full text |Cite
|
Sign up to set email alerts
|

The MESA Study

Abstract: This article examines the Mathematics, Engineering, Science Achievement (MESA) program and investigates its impact on underrepresented student populations. MESA was started in California during the 1970s to provide pathways to science, technology, engineering, and mathematics careers for underrepresented students and represents an exemplar model of informal learning environments. Using a mixed-method research design of investigation, this exploratory study looks at the relationship between MESA activities and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Successful examples of integrative programs include the Meyerhoff program at the University of Maryland, Baltimore County (Carter et al, 2009); the PEERS program at the University of California, Los Angeles (Toven-Lindsey et al, 2014); and the multi-state MESA program at the secondary level (Denson, 2017). However, Dyer-Barr (2014) has observed that, despite the existence of numerous programs to improve equity in STEM higher education, the actual rate of degree attainment (particularly at the post-baccalaureate level) by underrepresented minorities has remained significantly less than the rate of degree attainment by non-minority students.…”
Section: Educational Contextmentioning
confidence: 99%
“…Successful examples of integrative programs include the Meyerhoff program at the University of Maryland, Baltimore County (Carter et al, 2009); the PEERS program at the University of California, Los Angeles (Toven-Lindsey et al, 2014); and the multi-state MESA program at the secondary level (Denson, 2017). However, Dyer-Barr (2014) has observed that, despite the existence of numerous programs to improve equity in STEM higher education, the actual rate of degree attainment (particularly at the post-baccalaureate level) by underrepresented minorities has remained significantly less than the rate of degree attainment by non-minority students.…”
Section: Educational Contextmentioning
confidence: 99%